Michael Polanyi, Tacit Cognitive Relativist - Jacobs, Struan (Heythrop journal, 2001)
Celebrated as a theorist of science, and a source of stimulating ideas for theologians and philosophers of religion, Michael Polanyi explicitly denied cognitive relativism. Yet cognitive relativism, this paper suggests, is implied by Polanyi's account of conceptual frameworks and intellectual controversies. In ‘The Stability of Beliefs’ (1952) Polanyi understands conceptual frameworks (science, psychoanalysis, Azande witchcraft, Marxism) as embedded in, and as expressed in the use of, their own languages. The language-with-theory limits the range of discussable subjects, interprets relevant facts in its own terms, permits only certain questions to be asked, with answers to these questions serving to confirm the framework. In Polanyi's masterwork, Personal Knowledge (1958), these ideas inform his discussion of controversies over scientific frameworks and frameworks vying to become part of science. In each controversy, frameworks are logically disconnected, Polanyi foreshadowing the incommensurability thesis I argue that Polanyi's ideas satisfy recognised criteria of cognitive relativism. Perception is undetermined by objects and conditioned by language. Empirical propositions, in Polanyi's view, are accepted as true only within a conceptual framework. Polanyi regards supporters of logically disconnected frameworks as thinking differently, living in different worlds, speaking different languages and as experiencing communication failure. There is no framework-independent argument or evidence to distinguish any framework as the best available approximation to the truth. Frameworks are logically disconnected and incommensurable.